Conventional colonoscopy vs. cap-assisted colonoscopy: there are differences in colonoscopy performance? - Duarte-Chang, Calixto (2024)
Introduction: Colonoscopy is the standard method for colorectal cancer diagnosis. Despite the use of multiple devices, polyp and adenoma detection results have been inconsistent. Objectives: The main aim of this research is to determine if there have been differences between conventional colonoscopy (CC) and cap-assisted colonoscopy (CAC) in the diagnosis performance to detect adenomas. Materials and methods: This is a prospective randomized clinical trial that compares the diagnostic performance of CC and CAC in detecting adenomas in a public reference hospital. Results: We randomly assigned 131 patients to either CC (n=64) or CAC (n=67). Cap-assisted colonoscopy was associated with shorter cecal intubation times (6 min vs. 7,5 min, p=0.005) and a higher chance of intubating the ileum (RR = 1.62; 1.21-2.17). There was no statistical difference in the adenoma detection rates (RR: 1.62; 1.21-2.17) or polyp detection rates (RR: 1.07; 0.602-1.919) between CC and CAC. Conclusion: Cap-assisted colonoscopy was associated with a shorter duration of cecal intubation and a higher probability of ileum intubation. We did not find statistical differences in the adenoma detection rates. In the CAC arm, there was a trend to detect more adenoma in the right colon, although this difference was not statistically significant.